(untitled) (Praxis Educativa, 2022)
The objective of this work is to analyze to what extent the growing differentiation of the workforce affects the student body of secondary education for young and adults persons in Argentina in recent years. For this, different surveys performed by INDEC are used to carry out a statistical approach about the socioeconomic characteristics of EDJA secondary school student body throughout the country, seeking to determine the degree to which their reproduction conditions are mediated by situations such as unemployment, precarious employment and poverty, among other aspects. The results show that these students generally belong to sectors that are highly affected by the growing differentiation of the labor force, which is manifested in that they have more deteriorated living conditions than the average adult population.